Comparative genome analysis and evolutionary study of human pathogenic Yersinia species / Tan Shi Yang - Tan, Shi Yang (2017)
Yersinia is a Gram-negative bacterial genus that includes serious pathogens such as the Yersinia pestis which causes plague, and Yersinia pseudotuberculosis and Yersinia enterocolitica which cause gastrointestinal infections. The remaining species are generally considered to be non-pathogenic to humans. While their virulence mechanisms are well-characterized, the evolution of Yersinia pathogens are not well-understood. To understand the evolution of Yersinia pathogens and Yersinia enterocolitica subspecies, an exhaustive evolutionary and comparative genome studies on a total of 86 Yersinia genomes using different bioinformatics approaches were performed. Based on phylogenetic and the gene gain-and-loss analyses, Yersinia enterocolitica and Yersinia pseudotuberculosis-Yersinia pestis were determined as belonging to different phylogroups and have acquired different set of metabolism genes, suggesting that the evolution of human pathogenic Yersinia species is most probably triggered by ecological specialization. Besides, pairwise sequence comparisons showed that the ail virulence gene of Yersinia enterocolitica had higher sequence identities to the ail gene family (consists of both ail gene and homologs in the same family) of Yersinia pseudotuberculosis-Yersinia pestis compared to its own ail homolog, suggesting that the ail gene might have been duplicated in the latter species and then transferred laterally to Yersinia enterocolitica. Taken all together, it is proposed that the evolution of Yersinia is not in parallel, but rather accompanied by the gene gain-and-loss, gene duplication and lateral gene transfer. This contradicts finding of previous study that suggested the human pathogenic Yersinia species might have evolved in parallel to acquire the same virulence determinants. On the other hand, phylogenetic tree and gene gain-and-loss analyses in this study showed that Yersinia enterocolitica strains could be demarcated into three distinct phylogroups,with each of them acquiring different sets of putative metabolism genes. This postulates that ecological specialization might have triggered subspeciations in Yersinia enterocolitica species and lead to the emergence of highly pathogenic, low pathogenic and non-pathogenic subspecies, instead of two subspecies as previously reported. Data gathered in this study also suggest that the lateral gene transfer between subspecies in Yersinia enterocolitica might not be extensive as the gene content-based phylogenetic tree highly resembled supermatrix tree. Further virulence gene analyses showed that the ail gene was pseudogenized in the non-pathogenic subspecies, probably causing the loss of pYV virulence plasmid and pathogenicity in this subspecies. To facilitate the ongoing and future research of Yersinia, YersiniaBase, a robust and userfriendly Yersinia resource and comparative analysis platform for analysing Yersinia genomic data was developed. The AJAX-based real-time searching system was implemented to smooth the process of searching genomic data in large databases. YersiniaBase also has in-house developed tools: (1) Pairwise Genome Comparison tool for comparing two user-selected genomes; (2) Pathogenomics Profiling Tool for comparative virulence gene analysis of Yersinia genomes; (3) YersiniaTree for constructing phylogenetic tree of Yersinia. Successful applications of these useful tools was demonstrated in this study. Overall, this study provides better insights in elucidating the evolution of human pathogenic Yersinia and subspeciation in Yersinia enterocolitica. Lastly, the YersiniaBase will offer invaluable Yersinia genomic resource and analysis platform for the analysis of Yersinia in the future.